2005
DOI: 10.3171/ped.2005.103.1.0043
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of failure after endoscopic third ventriculostomy in young infants

Abstract: The authors' data strongly suggest that CSF pathway reclosure is the factor most responsible for ETV failure in obstructive hydrocephalus. According to both their experiences and to studies published in the literature, the formation of new arachnoid membranes or scars plays a far greater role in ETV failure than does poor CSF absorption, at least in aqueductal stenosis. It is hypothesized that infants have a higher tendency to form new arachnoid membranes than do older patients and that this factor may explain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
75
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(78 citation statements)
references
References 25 publications
2
75
0
1
Order By: Relevance
“…4,14 None of the hydrocephalus-related diagnoses in these data had a significant association with ETV success. While some authors reported no correlation of hydrocephalus etiology with ETV outcomes, 3,8,19,21 others have found etiology to be predictive of ETV success. 1,9,10 Etiology of hydrocephalus accounts for up to 33% of the possible points in the aforementioned ETV success score paradigm.…”
Section: Discussionmentioning
confidence: 99%
“…4,14 None of the hydrocephalus-related diagnoses in these data had a significant association with ETV success. While some authors reported no correlation of hydrocephalus etiology with ETV outcomes, 3,8,19,21 others have found etiology to be predictive of ETV success. 1,9,10 Etiology of hydrocephalus accounts for up to 33% of the possible points in the aforementioned ETV success score paradigm.…”
Section: Discussionmentioning
confidence: 99%
“…4,24,30,31 Determining the best candidates for ETV has been difficult, with conflicting reports on who are the best candidates, particularly regarding the effect of age and etiology. Reports have indicated that outcome is a function of age 23,32,33 independent of age, 1,34 a function of etiology, 1,35-37 or a function of both age and etiology. 38 More recent evidence from larger, and in one case, multicenter series has supported the finding that age is the main determinant of outcome with younger children, particularly neonates, faring worse.…”
Section: Discussionmentioning
confidence: 99%
“…This would favor failure of the stoma. A limited CSF absorptive capacity in the first few months could also potentially contribute to this ETV failure [34].…”
Section: Success Rates and Determinants Of Successmentioning
confidence: 99%
“…These studies seem to indicate that neuroendoscopy is a safe approach for the fenestration of suprasellar arachnoid cysts with a high success rate and low likelihood of necessary postprocedural shunting. For infants with large hemispheric arachnoid cysts, the success rate of endoscopic fenestration is less favorable than in older children; therefore, some authors advocate shunting those primarily in light of low endoscopic success rates [34,60]. The author will advocate a neuroendoscopic approach if possible.…”
Section: Arachnoid Cystsmentioning
confidence: 99%